2017
DOI: 10.1007/s40271-017-0232-1
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Chronic HCV-Infected Patients Switching to Pegylated-Interferon-Free Regimens (ANRS CO20 CUPIC Cohort Study and SIRIUS Trial)

Abstract: These results highlight an improvement in both physical and mental HRQL during HCV treatment, but no major improvement in physical HRQL after treatment end, when comparing PEG-IFN-free regimens with PEG-IFN-containing regimens. This suggests that in the PEG-IFN-free regimens era, screening and comprehensive care of comorbidities and residual somatic symptoms during treatment, and especially after HCV clearance, are still needed to improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…All-oral DAA regimens are much better tolerated and more effective than interferon-based regimens, and these differences are reflected in HRQOL. An analysis of HRQOL data in patients who received boceprevir or telaprevir plus pegylated interferon/ribavirin in the French CUPIC trial, and who were subsequently re-treated with an all-oral DAA regimen in the French SIRIUS trial, demonstrated significantly less impairment on both physical and mental component scores during treatment with the all-oral DAA regimen [86]. The results of a placebo-controlled trial suggest that improved patient-related outcomes with all-oral DAA regimens are attributable to suppression of viral replication.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…All-oral DAA regimens are much better tolerated and more effective than interferon-based regimens, and these differences are reflected in HRQOL. An analysis of HRQOL data in patients who received boceprevir or telaprevir plus pegylated interferon/ribavirin in the French CUPIC trial, and who were subsequently re-treated with an all-oral DAA regimen in the French SIRIUS trial, demonstrated significantly less impairment on both physical and mental component scores during treatment with the all-oral DAA regimen [86]. The results of a placebo-controlled trial suggest that improved patient-related outcomes with all-oral DAA regimens are attributable to suppression of viral replication.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%